A study on the influence of product environmental information transparency on online consumers’ purchasing behavior of green agricultural products - Fu, Shaoling; Ma, Ruili; He, Guangyao; Chen, Zhiyi; Liu, Hua (Frontiers in Psychology, 2023)
In 2020, the outbreak of COVID-19 has forced consumers to shift their consumption patterns online. However, the problem of online fraud in green agricultural products seriously undermines consumer trust and is detrimental to the sustainable consumption of green agricultural products. Therefore, it is particularly important to enhance consumers’ trust in online sellers. Based on signalling theory, this study constructs a theoretical framework of “product environmental information transparency - online consumer trust - online purchase behaviour”. A sample of 512 consumers with online purchase experience of green agricultural products was collected. A structural equation model was used to empirically investigate the influence of product environmental information transparency on online consumer trust and online purchase behaviour. The results show that (1) the two dimensions of product environmental information transparency have different effects on different dimensions of online consumer trust. Among them, soil information transparency has a significant positive effect on competence trust, while it does not have a significant positive effect on benevolence trust. The findings suggest that: (1) water information transparency has a significant positive effect on both dimensions of online consumer trust; (2) online consumer trust has a significant positive effect on online consumer purchase behaviour; (3) competence trust has a significant positive effect on benevolence trust. The findings help practitioners and policy makers to promote the sustainable development of green agriculture.